Erythropoietic effects of vadadustat in patients with anemia associated with chronic kidney disease. Issue 9 (15th July 2022) - Koury, Mark J.; Agarwal, Rajiv; Chertow, Glenn M.; Eckardt, Kai‐Uwe; Fishbane, Steven; Ganz, Tomas; Haase, Volker H.; Hanudel, Mark R.; Parfrey, Patrick S.; Pergola, Pablo E.; Roy‐Chaudhury, Prabir; Tumlin, James A.; et al.
Abstract: Patients with chronic kidney disease (CKD) develop anemia largely because of inappropriately low erythropoietin (EPO) production and insufficient iron available to erythroid precursors. In four phase 3, randomized, open‐label, clinical trials in dialysis‐dependent and non–dialysis‐dependent patients with CKD and anemia, the hypoxia‐inducible factor prolyl hydroxylase inhibitor, vadadustat, was noninferior to the erythropoiesis‐stimulating agent, darbepoetin alfa, in increasing and maintaining target hemoglobin concentrations. In these trials, vadadustat increased the concentrations of serum EPO, the numbers of circulating erythrocytes, and the numbers of circulating reticulocytes. Achieved hemoglobin concentrations were similar in patients treated with either vadadustat or darbepoetin alfa, but compared with patients receiving darbepoetin alfa, those receiving vadadustat had erythrocytes with increased mean corpuscular volume and mean corpuscular hemoglobin, while the red cell distribution width was decreased. Increased serum transferrin concentrations, as measured by total iron‐binding capacity, combined with stable serum iron concentrations, resulted in decreased transferrin saturation in patients randomized to vadadustat compared with patients randomized to darbepoetin alfa. The decreases in transferrin saturation were associated with relatively greater declines in serum hepcidin and ferritin in patients receiving vadadustat compared with those receiving darbepoetin alfa. These results for serum transferrin saturation, hepcidin, ferritin, and erythrocyte indices were consistent with improved iron availability in the patients receiving vadadustat. Thus, overall, vadadustat had beneficial effects on three aspects of erythropoiesis in patients with anemia associated with CKD: increased endogenous EPO production, improved iron availability to erythroid cells, and increased reticulocytes in the circulation.